WHAT THE GIANT TELLS US ABOUT AGREEING POST-VERBAL SUBJECTS IN XHOSA - Ström, Eva-Marie Bloom (Stellenbosch papers in linguistics plus, 2017)
Constructions with the subject following the verb are a widely studied topic in Bantu linguistics. One such construction, in which the subject is dislocated, is considered not as core subject inversion, but generally as an afterthought construction. This study takes a spoken text, in this case a narrative, as its point of departure to examine this kind of construction more carefully in terms of its function and morphosyntactic structure in Xhosa, a Bantu language of South Africa. The paper shows that such agreeing post-verbal subject constructions are used to re-activate semi-active concepts that have been mentioned previously in the narrative. They reintroduce a concept which then becomes the topic of the current sentence and of subsequent phrases, in which the subject is often pronominalized. It is also shown that the expected penultimate lengthening, one of the diagnostics used to differentiate core inversion from constructions with a dislocated subject, is often not present. The function of the construction and other morphosyntactic diagnostics point to the subject being dislocated, however. Furthermore, it is argued, based on a few examples from the narrative and follow-up grammaticality judgements, that there is agreeing inversion in Xhosa, with the subject in the immediately-after-verb position. This inversion construction has not previously been attested in Xhosa and further research is needed in order to corroborate the results. The appendix presents the recorded, transcribed, glossed and translated narrative on which the analysis is based.